First evidence of bacterial translocation from the intestinal tract as a route of Helicobacter cinaedi bacteremia. Issue 1 (8th December 2017) - Araoka, Hideki; Baba, Masaru; Okada, Chikako; Kimura, Muneyoshi; Sato, Tomoaki; Yatomi, Yutaka; Moriya, Kyoji; Yoneyama, Akiko
Abstract: Background: The route of Helicobacter cinaedi bacteremia has not yet been clarified. Although bacterial translocation from the intestinal tract into the circulation has been suggested, it has not been demonstrated thus far. The objective of this study was to investigate the port of entry of this bacterium. Material and Methods: We conducted a retrospective study on patients with H. cinaedi bacteremia between March 2009 and May 2013. Records of patients in whom H. cinaedi was detected in both blood and stool cultures were extracted. H. cinaedi was identified using gyrB‐targeted PCR. Pulse‐field gel electrophoresis was used to investigate the consistency of the genotypes. Results: Seventy‐one patients were diagnosed with H. cinaedi bacteremia during the study period. H. cinaedi was detected in both blood and stool samples of 21 patients. Pulse‐field gel electrophoresis was used to investigate the consistency of the genotypes in 18 evaluable strains (from 9 patients). The pulse‐field gel electrophoresis patterns of the stool‐ and blood‐derived strains of H. cinaedi were consistent among all 9 patients. Most of the 9 patients analyzed were immunocompromised and being treated with anticancer drugs or steroids, which suggests reduced intestinal immunity. Conclusions: This is the first study to demonstrate that bacterial translocation from the intestinal tract could represent one route of H. cinaedi bacteremia.